A coexistência de quatro ciclos limite em campos vetoriais seccionalmente lineares em R3 - ANDRADE, Kamila da Silva (2012)
In this work we study continuous, symmetric and piecewise linear vector fields on R3, we investigate the existence of limit cycles using the closing equations method. More specifically, we study a two parameters family of this vector fields and we show the coexistence of four limit cycles and too, its realization on Chua s circuit.